Optimizing Cash Waqf Linked Sukuk (CWLS) for Inclusive and Sustainable Economic Development in Indonesia - Budimansyah Budimansyah; Diah Mukminatul Hasyimi; Dimas Pratomo; Muslim Muslim; Saifuddin Amin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Sukuk has emerged as a governmental tool for acquiring private capital to finance ongoing infrastructure projects. This research seeks to assess the optimization of Cash Waqf Linked Sukuk (CWLS) for equitable and sustainable economic growth in Indonesia. The research approach used is a qualitative approach which focuses on analyzing the content of literature (literature research). The data used is secondary data originating from various reading sources in journals, books, and other libraries. The verification approach employs triangulation methods, whereas the data analysis method encompasses data reduction, data display, and data analysis. The findings indicated that the execution of CWLS engaged five stakeholders: Bank Indonesia as the implementation facilitator and Custodian Bank; the Indonesian Waqf Board (BWI) as the regulator, mentor, and nazhir overseeing waqf; and the Ministry of Finance as the SBSN issuer and fund manager in the real sector. Waqf monies are used to support economic and social initiatives aimed at enhancing the national economy, including the promotion of Islamic banking development. Funding productive assets, such as those used to establish company development incubators and generate employment via enterprises in the real sector, Facilitating the execution of social initiatives, establishment of Corporate Social Responsibility funds.